Bis(oxazolines) based on glycopyranosides – steric, configurational and conformational influences on stereoselectivity - Minuth, Tobias; Boysen, Mike M. K. (Beilstein Journal of Organic Chemistry, 2010)
In previous studies we found that the asymmetric induction of bis(oxazolines) based on D-glucosamine strongly depended on the steric demand of the 3-O-substituents. To further probe the impact of the 3-position of the pyranose scaffold, we prepared 3-epimerised and 3-defunctionalised versions of these ligands as well as a 3-O-formyl derivative. Application of these new ligands in asymmetric cyclopropanation revealed strong steric and configurational effects of position 3 on asymmetric induction, further dramatic effects of the pyranose conformation were also observed.
Keywords: asymmetric synthesis; carbohydrates; copper; cyclopropanation; ligand design